Absolute ambiguity: Predictive conjectures, rules of inference, and hermeneutic opacity in music. (De Musica, 2023)
The metasemantic nature of music does not allow forming inference rules useful for disambiguating the deep structure of a message, like any sound signal showing a minimum of structural coherence. The creation, exercise, decoding of musical practices is perennially poised between magic and science, between shamanic improvisation and the (often overestimated) competence of experts. Between the two is the taste of the public, notoriously fluctuating and changeable, not as the needle in the balance but as an additional element of cognitive undecidability. In the end, musical philology falls back on a mere criterion of probability, both analytical and predictive, or of absolute fungibility, having to deal both with the lability of the interpretative paradigms and with the relativity of what, in music, appears «obscure» and far from the argumentative «clarity» of epideictic or demonstrative rhetoric.